The family's perception of its presence at the pediatric and neonatal intensive care unit - Molina, Rosemeire Cristina Moretto; Fonseca, Elieth Lessa; Waidman, Maria Angélica Pagliarini; Marcon, Sonia Silva (Revista da Escola de Enfermagem da USP, 2009)
This qualitative-based study aimed to understand how families perceive their own presence at the Pediatric and Neonatal Intensive Care Unit, as well as the acceptance of their presence by healthcare workers. Data was collected through semi-structured interviews with 14 parents of children admitted to the pediatric and neonatal ICU at two hospitals in northwestern Paraná State, Brazil. Content analysis was chosen to interpret the data. The results revealed the suffering experienced by parents, the alteration of family dynamics resulting from the child's hospitalization, and the perception of the benefits of remaining close to the child in terms of welcoming and quality of care. It was concluded that parents value the professionals' respect and attention towards the child, thus creating bonds of affection, trust and gratitude for the care received.